2018
DOI: 10.23887/jpbj.v4i2.13343
|View full text |Cite
|
Sign up to set email alerts
|

Pelanggaran Dan Pematuhan Prinsip Kerjasama Pada Tuturan Humor Tensai Bakabon Volume 2 Karya Fujio Akatsuka

Abstract: ABSTRAK Penelitian ini bertujuan untuk mengetahui teknik humor dilihat dari segi kebahasaan dan bentuk pelanggaran maupun pematuhan prinsip kerjasama dalam manga Tensai Bakabon Volume 2. Penelitian ini menggunakan teori prinsip kerjasama yang dikemukakan oleh Grice (1975) dan teori teknik humor menurut Berger (1992). Data dalam penelitian ini diperoleh dengan menggunakan metode simak dan teknik catat kemudian dianalisis dengan metode deskriptif kualitatif. Hasil yang ditemukan yaitu sembilan teknik humor yang … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…He found that specific words in the Javanese of Samin people reflects the world view of its speakers which is influenced by the ideology of Saminism. Meanwhile, Fatmawati (2017) discusses the uniqueness of the Javanese of Samin people from the aspect of the principles of cooperation in communication. In speaking, the Samin people violate these principles so that it causes misunderstanding to others.…”
Section: Introductionmentioning
confidence: 99%
“…He found that specific words in the Javanese of Samin people reflects the world view of its speakers which is influenced by the ideology of Saminism. Meanwhile, Fatmawati (2017) discusses the uniqueness of the Javanese of Samin people from the aspect of the principles of cooperation in communication. In speaking, the Samin people violate these principles so that it causes misunderstanding to others.…”
Section: Introductionmentioning
confidence: 99%